Digital Violence in the School Environment. A Growing Challenge to Confront - بوزريعة, ايمان; زرقي, عائشة; عدار, الزهراء (مجلة دراسات في سيكولوجية الانحراف, 2023)
This article explores the rising concern of digital violence in educational settings, highlighting challenges and effective strategies for prevention. Analyzing diverse forms of digital violence, including cyberbullying and harmful content dissemination, it uncovers contributing factors such as individual traits, familial dynamics, and technological advancements. The article underscores the significance of a comprehensive approach involving educators, parents, and policymakers to combat digital violence. It advocates for educational initiatives, teacher training, robust institutional policies, community partnerships, and media literacy programs tailored to the Algerian context. By swiftly responding to victims' needs, safeguarding academic well-being, and fostering a respectful digital culture, this article envisions a safer digital landscape for the upcoming generation.